FEATURES OF CLINICAL FLOW, METABOLISM AND SYSTEM HEMODYNAMICS AT ICD AT PATIENTS OF DM OF TYPE 2 WITH RENAL DISFUNCTION - Погребняк, О.О. (World of Medicine and Biology, 2012)
For patients by the diabetes mellitus of type 2 with renal disfunction the flow of ischemic heart disease is characterized by the increase of frequency of origin (to prevalence) of arterial pressure, as compared to patients by ischemic heart disease noninfringement carbohydrate exchange. Ischemic heart disease for patients by the diabetes mellitus of type 2 with renal disfunction accompanied by the appropriate increase of levels of glicemia on an empty stomach and HBA1c. The protracted violation of carbohydrate exchange assists progress of ischemic heart disease at the diabetes mellitus of type 2, and the increase of mass of body influences on frequency of origin (prevalence) of arterial pressure at ischemic heart disease.
Keywords: diabetes mellitus; renal disfunction; arterial pressure